Students' perceptions towards academic integrity: a study among ACIS students in UiTM Puncak Alam / Nur Asyiqin Nordin - Nordin, Nur Asyiqin (2019)
This research is done to examine students’ attitude and perceptions on academic integrity because the problem of academic dishonesty is an unceasing problem in educational institutions globally. The method used in this study is a quantitative online questionnaire survey on respondents’ views and engagements in academic misconducts, mainly cheating and plagiarism. Findings disclosed that students’ acceptance towards academic dishonesty decreased as they study longer in the university and also students are more lenient in cheating during tests compared to final examinations. The findings of this study will surely help in the improvement of the implementation of academic integrity in educational institutions as the factors and preventive solutions have also been discussed.